Vietnam science and technology policy: Opportunities and challenges - tap, Ban Bien (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
This paper was compiled from studies, discussions and exchanges of the National Institute for Science and Technology Policy and Strategy Studies. The paper pointed out the role of science and technology (S&T) in different stages of economic development, requirements for S&T policy, current orientations and policies, and clearly indicated opportunities, challenges for S&T policy development and the way to respond to challenges. Code: 14050701